Analisis Ketimpangan Pendapatan di Indonesia Periode 2017-2023 (Studi kasus 34 Provinsi di Indonesia) - Haidar Akhmad Al Barabasi; Hastarini Dwi Atmanti (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2025)
This research examines the analysis of the influence of income inequality in a case study of 34 provinces in Indonesia for the 2017-2024 period. The method in this research uses panel data regression analysis, with secondary data obtained from BPS. In partial research results, the unemployment rate and poverty rate variables have a positive effect. significant to income inequality, while the variables HDI and Open Investment have a negative effect on income inequality, simultaneously the Unemployment Rate, HDI, Poverty Level and Open Investment together or simultaneously have a significant effect on income inequality.